2014
DOI: 10.1111/vru.12137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Standard Magnetic Resonance Characteristics Used to Differentiate Neoplastic, Inflammatory, and Vascular Brain Lesions in Dogs

Abstract: Magnetic resonance (MR) imaging characteristics are commonly used to help predict intracranial disease categories in dogs, however, few large studies have objectively evaluated these characteristics. The purpose of this retrospective study was to evaluate MR characteristics that have been used to differentiate neoplastic, inflammatory, and vascular intracranial diseases in a large, multi‐institutional population of dogs. Medical records from three veterinary teaching hospitals were searched over a 6‐year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
87
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 47 publications
(112 reference statements)
2
87
0
2
Order By: Relevance
“…Investigators in 1 study 4 found that 7 MRI characteristics were significantly more common in patients with neoplasia than in patients with inflammatory and vascular disease. In a more recent study, 5 investigators found that only strong contrast enhancement was significantly more common in neoplastic lesions. Despite this lack of specificity regarding individual findings, conventional MRI has reasonable overall specificity for differentiating between broad etiologic categories of intracranial disease (neoplastic, inflammatory, or cerebrovascular).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Investigators in 1 study 4 found that 7 MRI characteristics were significantly more common in patients with neoplasia than in patients with inflammatory and vascular disease. In a more recent study, 5 investigators found that only strong contrast enhancement was significantly more common in neoplastic lesions. Despite this lack of specificity regarding individual findings, conventional MRI has reasonable overall specificity for differentiating between broad etiologic categories of intracranial disease (neoplastic, inflammatory, or cerebrovascular).…”
mentioning
confidence: 95%
“…Conventional MRI allows for evaluation of intracranial lesions and interpretation based on inherent macroscopic properties of the lesions (location, signal intensity, contrast enhancement, edema, and hemorrhage). Investigators in other studies 4,5 have found that conventional MRI findings for inflammatory and neoplastic lesions are often nonspecific, with overlapping imaging findings for the 2 conditions. Investigators in 1 study 4 found that 7 MRI characteristics were significantly more common in patients with neoplasia than in patients with inflammatory and vascular disease.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…, Young et al . ), as a final confirmative post mortem diagnosis was only obtained in three dogs. Fortunately, most dogs recovered from the acute neurological event and, as a consequence, owners were not motivated for post mortem investigation in dogs that were later euthanased due to unrelated causes.…”
Section: Discussionmentioning
confidence: 98%
“…It was presumed that masses, especially those with defined margins, represent the lesion type that is least dependent on subtle differences in signal intensity to detect. Only records from animals with meningoencephalitis were searched in creation of the group with expected lesions, because masses are found less commonly in inflammatory brain disease than in neoplastic or vascular brain diseases, and inflammatory brain lesions rarely have defined margins . However we did not exclude animals with mass effect, and therefore did not eliminate the influence of mass effect on lesion detection altogether.…”
Section: Discussionmentioning
confidence: 99%